Protease/peptidase (Flavourzyme) pretreatment on palm kernels improves the aroma of resultant palm kernel oil after kernel roasting. Issue 8 (15th March 2017) - Zhang, Wencan; Zhao, Fangju; Yang, Tiankui; Liu, Shaoquan
Abstract : The aroma of palm kernel oil (PKO) affects its application. Aiming to improve its aroma quality, the effects of protease/peptidase (Flavourzyme) pretreatment on the palm kernels (PK) before kernel roasting were investigated. The results showed that more pyrazines (6.7‐, 10‐, 3.4‐fold) were found in PKO derived from treated PK after light, medium, and dark kernel roasting, respectively, compared to the corresponding control, as detected by headspace (HS) – solid phase microextraction (SPME) coupled with gas chromatography (GC) – mass spectrometer (MS), and flame ionisation detector (FID) (HS‐SPME‐GC‐MS/FID). Principal component analysis (PCA) based on aroma‐active compounds revealed that after kernel roasting, the control oil was more correlated with O ‐heterocyclic compounds while the oil from treated PK was more closely related to N ‐heterocyclic compounds. Sensory evaluation further indicated that after Flavourzyme pretreatment, the obtained PKO (with medium kernel roasting degree) possessed more nutty, roasty, and caramelic flavor notes. These aroma changes could be attributed to the altered aroma precursors in PK due to Flavourzyme treatment, of which 1.5‐ and 20.7‐fold increments of soluble sugars and free amino acids were found. This study demonstrated that by enriching thermal reaction reactants, Flavourzyme is capable of positively modifying the aroma of PKO after kernel roasting. Practical applications: Flavourzyme pretreatment followed by roasting rendered the resultant PKO a more nutty, roasty, and caramelic aroma. Such improvement in aroma would not only be beneficial for the current utilization of PKO especially in bakery and confectionery areas, but also widen the scope of its applications. Besides, enzyme pretreatment combined with the thermal reactions, which was the first time applied in the aroma modification of seeds oils, was demonstrated to be an effective approach for aroma modulation. Flavourzyme pretreatment of palm kernel (PK) was proved to be able to significantly increase the content of pyrazine in the resultant palm kernel oil (PKO) after different degrees of kernel roasting. As expected, more nutty, roasty, and caramelic sensory notes were found in PKO produced by enzyme treated PK than that of the control. Abstract : Flavourzyme pretreatment of palm kernel (PK) was proved to be able to significantly increase the content of pyrazine in the resultant palm kernel oil (PKO) after different degrees of kernel roasting. As expected, more nutty, roasty, and caramelic sensory notes were found in PKO produced by enzyme treated PK than that of the control.